GREEN SUPPLY CHAIN MANAGEMENT: PERSPECTIVES OF EMPLOYEES ON HOSPITALITY AND TOURISM SECTORS IN WEST SUMATERA - Meuthia, Meuthia; Lita, Ratni Prima; Faisal, Ranny Fitriana (TRIKONOMIKA, 2019)
This study aims to analyze employee perceptions regarding the implementation of Green Supply Chain Management (GSCM) in the hospitality & tourism sector in West Sumatra. GSCM reflected by the dimensions of internal environmental management and green purchasing can be influenced by environmental orientation (internal and external environmental orientation). GSCM are tested at the second-order construct reflective level and first-order reflective level. Linkages between variables in this study were identified through quantitative explanatory research techniques by testing hypotheses. Non-probability sampling through purposive sampling method from 77 respondents is carried out directly in the two main sectors. The results showed that all hypotheses had a significant effect. Internal environmental orientation and external environmental orientation have a significant effect on GSCM. Interestingly, environmental orientation has become an important predictor affecting the application of GSCM in the hospitality and tourism sector in West Sumatra.